Dual Mode Antibacterial Activity of Ion Substituted Calcium Phosphate Nanocarriers for Bone Infections - Sampath Kumar, T. S.; Madhumathi, K.; Rubaiya, Y.; Doble, Mukesh (Frontiers in Bioengineering and Biotechnology, 2015)
Nanotechnology has tremendous potential for the management of infectious diseases caused by multi-drug resistant (MDR) bacteria, through the development of newer antibacterial materials and efficient modes of antibiotic delivery. Calcium phosphate (CaP) bioceramics are commonly used as bone substitutes due to their similarity to bone mineral and are widely researched upon for the treatment of bone infections associated with bone loss. CaPs can be used as local antibiotic delivery agents for bone infections and can be substituted with antibacterial ions in their crystal structure to have a wide spectrum, sustained antibacterial activity even against drug resistant bacteria. In the present work, a dual mode antibiotic delivery system with antibacterial ion substituted calcium deficient hydroxyapatite (CDHA) nanoparticles has been developed. Antibacterial ions such as zinc, silver and strontium have been incorporated into CDHA at concentrations of 6 at. %, 0.25-0.75 at. % and 2.5-7.5 at. % respectively. The samples were found to be phase pure, acicular nanoparticles of length 40-50 nm and width 5-6 nm approximately. The loading and release profile of doxycycline, a commonly used antibiotic, was studied from the nanocarriers. The drug release was studied for five days and the release profile was influenced by the ion concentrations. The release of antibacterial ions was studied over a period of 21 days. The ion substituted CDHA samples were tested for antibacterial efficacy on S.aureus and E.coli by MIC/MBC studies and time-kill assay. AgCDHA and ZnCDHA showed high antibacterial activity against both bacteria while SrCDHA was weakly active against S.aureus. Present study shows that the antibiotic release can provide the initial high antibacterial activity and the sustained ion release can provide a long-term antibacterial activity. Such dual mode antibiotic and antibacterial ion release offers an efficient and potent way to treat an incumbent drug resistant infection.